RIGHT TO EDUCATION AND JUVENILE COURT JURISDICTION AT THE BRAZILIAN STJ: AN ANALYSIS OF THESES JOURNALS 245 AND 250 - Fogatti, Laura Mauro Feitoza; Fogatti, Osvaldo de Freitas (Seven Editora, 2025)
Considering the centrality of the fundamental right to education in the 1988 Brazilian Constitution and in the Child and Adolescent Statute (ECA), this article critically examines recent case law of the Superior Court of Justice (STJ) consolidated in Theses Journals nos. 245 and 250, focusing on decisions concerning education/teaching. A qualitative, documentary review was conducted to analyze the theses and leading precedents (e.g., Theme 1,058 on the Juvenile Court’s absolute jurisdiction over school enrollment claims; and the recognition of a subjective right to elementary education for children under six and the suitability of public civil actions). Findings indicate that the STJ underscores the non‑waivable nature of the right to education, the primacy of the best interests of the child, and the ECA’s special protective regime, including rules on competence (immediate forum) and procedural tools. We conclude that these guidelines constrain education policies and direct institutional action (Public Prosecutor’s Office, Public Defenders and government agencies), strengthening effective judicial protection and the implementation of adequate conditions for access to and permanence in school.